Slow Photons for Photocatalysis and Photovoltaics. Issue 17 (6th February 2017) - Liu, Jing; Zhao, Heng; Wu, Min; Van der Schueren, Benoit; Li, Yu; Deparis, Olivier; Ye, Jinhua; Ozin, Geoffrey A.; Hasan, Tawfique; Su, Bao‐Lian
Abstract : Solar light is widely recognized as one of the most valuable renewable energy sources for the future. However, the development of solar‐energy technologies is severely hindered by poor energy‐conversion efficiencies due to low optical‐absorption coefficients and low quantum‐conversion yield of current‐generation materials. Huge efforts have been devoted to investigating new strategies to improve the utilization of solar energy. Different chemical and physical strategies have been used to extend the spectral range or increase the conversion efficiency of materials, leading to very promising results. However, these methods have now begun to reach their limits. What is therefore the next big concept that could efficiently be used to enhance light harvesting? Despite its discovery many years ago, with the potential for becoming a powerful tool for enhanced light harvesting, the slow‐photon effect, a manifestation of light‐propagation control due to photonic structures, has largely been overlooked. This review presents theoretical as well as experimental progress on this effect, revealing that the photoreactivity of materials can be dramatically enhanced by exploiting slow photons. It is predicted that successful implementation of this strategy may open a very promising avenue for a broad spectrum of light‐energy‐conversion technologies. Abstract : Slow photons can dramatically enhance the photoreactivity of semiconducting materials . It is believed that "slow photons" will break new ground to improve light harvesting of various materials for all solar‐related applications in the future.